Differences in metabolic-energy potential in u16 football players (cadet age) in relation to competition level - Andrašic, S.; Cvetkovic, M.; Milic, Z. (Sports Science and Health, 2016)
In order to determine the difference in metabolicenergy potential in U16 football players (cadet age) at different levels of competition, a survey was conducted on a sample of sixty players aged 14 to 16. The sample of respondents is divided into the following subsamples: players of Serbian national football team (n=20), players from highquality league of Vojvodina (n=21) and the players from the regional competition levels (n=19). The lactate blood level was determined by testing capillary blood from the finger during three stages of Cooper test: the concentration of lactate in the standstill stage was measured before the start of the test - before the load; the concentration of lactate during the load stage was measured one minute after completion of the test; and the concentration of lactate in the recovery stage was measured in the tenth minute of recovery. The survey results indicate a statistically significant difference between the said groups of players in relation to the analyzed metabolic-energy parameters of the players.